World real interest rates: A global savings and investment perspective - Brigitte Desroches; Michael Francis (Bank of Canada, 2007)
Over the past 15 years, long-term interest rates have declined to levels not seen since the 1970s. This paper explores possible shifts in global savings and investment that have led to this fall in the world real interest rate. There are several key findings. First, the authors identify the relative weakness in investment demand as more important than the relative increase in desired global savings to explain the decline in global interest rates. Second, the results indicate that the key factors explaining movements in savings and investment are variables that evolve relatively slowly over time, such as labour force growth and age structure. The conclusions suggest that over the coming years, world real interest rates are likely to continue to adjust slowly, reflecting longterm trends.
Keywords: E2; E4; F3; 330; Interest rates; International topics; Investition; Sparen; Realzins; Erwerbspersonenpotenzial; Altersstruktur der Bevölkerung; Welt